Design and performance of a manual extruder for recycled plastic-brick composite pavers - Daikh, Abdelkader; Moulai Arbi, Youcef; Bentahar, Mohammed; Mahmoudi, Noureddine (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: This study aimed to develop a cost-effective manual plastic brick extruder for manufacturing composite bricks from recycled polypropylene and brick powder. The goal was to address housing challenges in developing countries while promoting sustainable waste management. Methods: A single screw extruder with a 60 mm die was fabricated, featuring a manual crank, a heating system, and a hopper. Composite specimens with varying polypropylene (30-80 weight percentages) and brick powder (20-70 weight percentages) ratios were produced. Mechanical testing was conducted, including compressive strength, flexural strength, impact resistance, and density measurements. Results: The 40:60 polypropylene:brick powder mixture exhibited optimal compressive strength, ranging from 23.76-24.90 MPa. Flexural strength peaked at the 50:50 ratio (11.86-12.5 MPa). Impact resistance decreased with increasing brick powder content. Density increased linearly with brick powder content, ranging from 1.48-1.77 g/cm³. The extruder successfully produced uniform composite specimens across all mixtures. Conclusions: The study demonstrated the feasibility of producing composite bricks using a low-cost, manually operated extruder. Two optimal mixture compositions were identified: 40:60 polypropylene:brick powder for maximum compressive strength and 50:50 for optimal flexural strength. This approach offers a promising solution for affordable housing construction while addressing plastic waste management in developing regions. Future research should focus on optimizing the extrusion process, exploring additional waste materials, and conducting long-term durability studies of composite bricks.